Methamphetamine and HIV-Tat Protein Synergistically Induce Oxidative Stress and Blood-Brain Barrier Damage via Transient Receptor Potential Melastatin 2 Channel - Huang, Jian; Zhang, Ruilin; Wang, Shangwen; Zhang, Dongxian; Leung, Chi-Kwan; Yang, Genmeng; Li, Yuanyuan; Liu, Liu; Xu, Yue; Lin, Shucheng; Wang, Chan; Zeng, Xiaofeng; et al. (Frontiers in Pharmacology, 2021)
Synergistic impairment of the blood-brain barrier (BBB) induced by methamphetamine (METH) and HIV-Tat protein increases the risk of HIV-associated neurocognitive disorders (HAND) in HIV-positive METH abusers. Studies have shown that oxidative stress plays a vital role in METH- and HIV-Tat-induced damage to the BBB but have not clarified the mechanism. This study uses the human brain microvascular endothelial cell line hCMEC/D3 and tree shrews to investigate whether the transient receptor potential melastatin 2 (TRPM2) channel, a cellular effector of the oxidative stress, might regulate synergistic damage to the BBB caused by METH and HIV-Tat. We showed that METH and HIV-Tat damaged the BBB in vitro, producing abnormal cell morphology, increased apoptosis, reduced protein expression of the tight junctions (TJ) including Junctional adhesion molecule A (JAMA) and Occludin, and a junctional associated protein Zonula occludens 1 (ZO1), and increased the flux of sodium fluorescein (NaF) across the hCMEC/D3 cells monolayer. METH and HIV-Tat co-induced the oxidative stress response, reducing catalase (CAT), glutathione peroxidase (GSH-PX), and superoxide dismutase (SOD) activity, as well as increased reactive oxygen species (ROS) and malonaldehyde (MDA) level. Pretreatment with n-acetylcysteine amide (NACA) alleviated the oxidative stress response and BBB damage characterized by improving cell morphology, viability, apoptosis levels, TJ protein expression levels, and NaF flux. METH and HIV-Tat co-induced the activation and high protein expression of the TRPM2 channel, however, early intervention using 8-Bromoadenosine-5'-O-diphosphoribose (8-Br-ADPR), an inhibitor of TPRM2 channel, or TRPM2 gene knockdown attenuated the BBB damage. Oxidative stress inhibition reduced the activation and high protein expression of the TRPM2 channel in the in vitro model, which in turn reduced the oxidative stress response. Further, 8-Br-ADPR attenuated the effects of METH and HIV-Tat on the BBB in tree shrews—namely, down-regulated TJ protein expression and increased BBB permeability to Evans blue (EB) and NaF. In summary, the TRPM2 channel can regulate METH- and HIV-Tat-induced oxidative stress and BBB injury, giving the channel potential for developing drug interventions to reduce BBB injury and neuropsychiatric symptoms in HIV-infected METH abusers.